2019
DOI: 10.4067/s0718-221x2019005000307
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to wood protection: Preliminary study of biologically synthesized copper oxide nanoparticle formulation as an environmental friendly wood protectant against decay fungi and termites

Abstract: Nanoparticles have addressed many challenges in science and technology and wood science research is one such field that has benefitted from application of metal nanoparticles. The metal nanoparticles that are commercially available for wood protection are synthesised by physical and chemical methods which produces toxic by-products and are expensive. The current study deals with a new approach for utilization of metal nanoparticle for wood protection in an ecofriendly and cost effective way. Metal nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Fresh leaves of Lantana camara (Lantana) were collected from Nallal, Karnataka and were used for the synthesis of CuO and ZnO nanoparticles. Leaf extract 20 % by weight was prepared as per the procedure adopted by Shiny et al (2019). Precursor solution of CuSO 4 , 5H 2 O and Zn (NO 3 ) 2 , 6H 2 O were prepared (0,025M) and preheated separately in a water bath at 60 °C for 30 minutes.…”
Section: Synthesis Of Copper Oxide and Zinc Oxide Nanoparticles By Using Lantana Camara Leaf Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…Fresh leaves of Lantana camara (Lantana) were collected from Nallal, Karnataka and were used for the synthesis of CuO and ZnO nanoparticles. Leaf extract 20 % by weight was prepared as per the procedure adopted by Shiny et al (2019). Precursor solution of CuSO 4 , 5H 2 O and Zn (NO 3 ) 2 , 6H 2 O were prepared (0,025M) and preheated separately in a water bath at 60 °C for 30 minutes.…”
Section: Synthesis Of Copper Oxide and Zinc Oxide Nanoparticles By Using Lantana Camara Leaf Extractmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) coupled with Energy dispersive analysis X-ray (EDAX) was used for the characterization of the synthesised CuO and ZnO nanoparticles as per the method described by Shiny et al (2019).…”
Section: Characterization Of Biologically Synthesized Cuo and Zno Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a synthesis pathway based on sustainable plant extracts for metallic nanoparticles allows the possibility of combining the intrinsic property of the plant extract and the metallic nanoparticles for a potential application in wood protection. The resulting formulation can protect the wood from biodeterioration in a more efficient way, without damaging the environment [119]. In another study, Akhtari M. and D. Nicholas tested and compared the effectiveness of CuO and ZnO nanoparticles as potential wood consolidants.…”
Section: Physico-chemical and Mechanical Propertiesmentioning
confidence: 99%
“…6). Whereas according to (Shiny et al, 2019) metal nanoparticles were effective in controlling microbial and termite demage to the wood. Another study has reported that nano-zinc-borate was effective enough to inhibit termites and the total mass loss of wood was only 5.2-5.4% (Mantanis et al, 2014).…”
Section: Evaluation Of Termite Damage To Treated Feeder Blocksmentioning
confidence: 99%